2016
DOI: 10.1080/07370016.2016.1227212
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ Perceptions of Worksite Health-Promotion Educational Activities

Abstract: Adults spend a significant amount of time at work making the worksite a convenient venue for participation in health-promotion activities. This research project examined participants' perceptions of gaining knowledge and changing health behavior practices as a result of knowledge gained through participation in health-promotion activities provided at the worksite. The worksite health-promotion activities were offered as a result of an innovative collaboration effort between nursing faculty in an academic setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Older employees may notice a deterioration in their physical health, and therefore, be ready to make health and wellness changes. This hypothesis aligns with existing research that found that as age increases, so does knowledge gain related to various health behaviors (Abell & Main, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Older employees may notice a deterioration in their physical health, and therefore, be ready to make health and wellness changes. This hypothesis aligns with existing research that found that as age increases, so does knowledge gain related to various health behaviors (Abell & Main, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Research has highlighted numerous benefits associated with worksite wellness programs (Abell & Main, ; Beck, Hirth, Jenkins, Hirth, Jenkins, Sleemand, & Zhang, ; Carter, Kelly, Alexander, & Holmes, ). Wellness programs traditionally focus on achieving outcomes such as reductions in medical costs, lowered employee health risks, decreased absenteeism and improved morale, with increased productivity also being examined (HERO, ; Rajaratnam, Sears, Shi, Coverley, & Pope, ).…”
Section: Introductionmentioning
confidence: 99%